Collective Bargaining on Working Time: Recent European Experiences - Thomas, Mark (Relations industrielles / Industrial Relations, 2008)
Collective Bargaining on Working Time: Recent European Experiences, edited by Maarten Keune, and Bela Galgoczi, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Collective bargaining; Flexible hours; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Working hours